Evaluasi dan Perbaikan Pengalaman Pengguna pada E-learning SMKN 12 Malang menggunakan Metode Goal Directed Design (GDD) - Muhammad Zidane Hidayatullah Suprapto; Retno indah Rokhmawati; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Teaching and learning activities in schools began to experience changes and were adapted to the development of information technology, resulting in changes and shifts in the educational paradigm. Due to the COVID-19 pandemic, the education system has adapted to distance learning, one of which is e-learning. In this study involved 3 people to be interviewed and 30 respondents in filling out the questionnaire. Preliminary data obtained from research activities show that e-learning users experience difficulties, namely the display is still standard (plain) and lacks supporting features. Visual appearance in an e-learning is a very influential aspect to make it easier to understand learning material, communicate key concepts and attract the attention of users or students. Based on these problems, researchers have a goal to redesign the e-learning of SMKN 12 Malang using the GDD (Goal-Directed Design) method that focuses on user goals and behavior in using e-learning. This method has 6 stages, namely research, modeling, requirements definition, framework definition, refinement and support. This study uses the Technique for User Experience Evaluation in E-learning (TUXEL) method to evaluate usability, pedagogical usability and user experience. Based on testing using the TUXEL method, the redesign in this study has increased.